Multifunction Drawing Table (MDT) / Nurazlina Jamalludin...[et al.] - Jamalludin, Nurazlina; Mat Noor, Mohamat Najib; Md Hashim, Azhari; Mohd Noor, Mohd Aiman Afiq; Rusli, Amirul Aswad (Universiti Teknologi MARA, Kedah, 2018)
Multifunction Drawing Table (MDT) offers practicality yet functionality which can be enhanced by the artists or designers in producing their 'artworks.This table was designed signed to provide a multifunctional table as it combines four different types of purposes and is invented to solve an artist's or designer's problem during their activity.The design integrates various function such as a cutting ma for cutting work, light box for tracing work, and as ai easel for drawing and writing tools.